Observing electron localization in a dissociating H2+ molecule in real time - H. Xu (Nature Portfolio, 2017)
Time resolved measurements provide insights to the intriguing process of ultrafast molecular fragmentation. Here the authors use CEP-locked laser pulses in pump–probe scheme to explore the H2+dissociation and find out that the electron localization to one of the nuclei occurs in about 15 fs.